Mercury immune toxicity in harbour seals: links to in vitro toxicity - Mazzucchelli Gabriel; Fonfara Sonja; Di-Poï Carole; Dupont Aurélie; Gillet Audrey; Siebert Ursula; Das Krishna; De Pauw Edwin; De Pauw-Gillet (BMC, 2008)
Abstract Background Mercury is known to bioaccumulate and to magnify in marine mammals, which is a cause of great concern in terms of their general health. In particular, the immune system is known to be susceptible to long-term mercury exposure. The aims of the present study were (1) to determine the mercury level in the blood of free-ranging harbour seals from the North Sea and (2) to examine the link between methylmercury in vitro exposure and immune functions using seal and human mitogen-stimulated peripheral blood mononuclear cells (T-lymphocytes). Methods Total mercury was analysed in the blood of 22 harbour seals. Peripheral blood mononuclear cells were isolated from seals (n = 11) and from humans (n = 9). Stimulated lymphocytes of both species were exposed to functional tests (proliferation, metabolic activity, radioactive precursor incorporation) under increasing doses of methylmercury (0.1 to 10 μM). The expression of cytokines (IL-2, IL-4 and TGF-β) was investigated in seal lymphocytes by RT-PCR and by real time quantitative PCR (n = 5) at methylmercury concentrations of 0.2 and 1 μM. Finally, proteomics analysis was attempted on human lymphocytes (cytoplasmic fraction) in order to identify biochemical pathways of toxicity at concentration of 1 μM (n = 3). Results The results showed that the number of seal lymphocytes, viability, metabolic activity, DNA and RNA synthesis were reduced in vitro, suggesting deleterious effects of methylmercury concentrations naturally encountered in free-ranging seals. Similar results were found for human lymphocytes. Functional tests showed that a 1 μM concentration was the critical concentration above which lymphocyte activity, proliferation and survival were compromised. The expression of IL-2 and TGF-β mRNA was weaker in exposed seal lymphocytes compared to control cells (0.2 and 1 μM). Proteomics showed some variation in the protein expression profile (e.g. vimentin). Conclusion Our results suggest that seal and human PBMCs react in a comparable way to MeHg in vitro exposure with, however, larger inter-individual variations. MeHg could be an additional cofactor in the immunosuppressive pollutant cocktail generally described in the blood of seals and this therefore raises the possibility of additional additive effects in the marine mammal immune system.